Task complexity reveals expertise of table tennis players - Padulo, Johnny; Pizzolato, Fabio; Rodrigues, Sergio Tosi [UNESP]; Migliaccio, Gian Mario; Attene, Giuseppe; Curcio, Raffaele; Zagatto, Alessandro Moura [UNESP] (My University, 2015)
AIM: The purpose of this study was to examine the effect of intensive practice in table-tennis on perceptual, decision-making and motor-systems. Groups of elite (HL=11), intermediate (LL=6) and control (CC=11) performed tasks of different levels. METHODS: All subjects underwent to reaction-time-test and response-time-test consisting of a pointing task to targets placed at distinct distances (15 and 25-cm) on the right and left sides. The ball speed test in forehand and backhand condition just for HL and LL group. RESULTS: In CC group reaction time was higher compared to HL (P< 0.05) group. In the response-time-test, there was a significant main effect of distance (P< 0.0001) and the tennis-table expertise (P= 0.011). In the ball speed test the HL were constantly faster compared to the LL in both forehand stroke (P< 0.0001) and backhand stroke (P< 0.0001). Overall, the forehand stroke was significantly faster than the backhand stroke. CONCLUSION: We can conclude that table-tennis-players have shorter response-times than non-athletes and the tasks of reaction-time and response-time are incapable to distinguish the performance of well-trained table tennis players of the intermediate player, but the ball speed test seems be able to do it.